Studi Netnotgrafi: Analisis Sentimen Rakyat Inggris Terhadap Imigran Ilegal dalam Platform X - Radithya Rahim Basmala; Muthi Najwa Hanifa; Semeion El Sozo; Deasy Silva Sari; Dina Yulianti (Jurnal Transformasi Global, 2025)
This study aims to explore public sentiment in the United Kingdom toward illegal immigrants through a netnographic analysis of the social media platform X (formerly Twitter). Using a qualitative approach, data were collected from posts, comments, and user interactions that discussed the issue of illegal immigration over a specified time period. The findings reveal a wide spectrum of public opinions influenced by factors such as economic conditions, national security concerns, media representation, and political ideology. The sentiments ranged from strong support for human rights to firm rejection of illegal immigrants, often accompanied by xenophobic narratives. This research highlights how social media serves as a space for the articulation of public identity, fears, and expectations regarding immigration policy. The study seeks to contribute to the development of more responsive and inclusive public policies on immigration in the UK.